Al-Tasrif li man ‘Ajiza ‘an al-Ta’lif oleh al-Zahrawi: Manfaatnya dalam Perkembangan Bidang Perubatan di Eropah: Al-Tasrif li man ‘Ajiza ‘an al-Ta’lif by al-Zahrawi: Its Benefit in the Development of the Field of Medicine in Europe - Karim, Nur Aqilah; Sidik@Mat Sidek, Roziah (Journal of Al-Tamaddun, 2021)
Al-Zahrawi was an illustrious figure in medicine. He not only contributed to the Islamic civilization, but is highly regarded as a genius who had an enormous influence, generally, in the field of medicine and, particularly, in surgery in Europe. His influence continued into the Renaissance age and the modern age. Renaissance was the age of European civilization from about the 14th Century to 17th Century AD which is said to be a period of ‘rebirth’ of arts, architecture, culture, politics, economics and knowledge. This influence is associated with his work, namely, al-Tasrif li man ‘Ajiza ‘an al-Ta’lif, which contains descriptions and illustrations of more than 200 surgical instruments and surgical procedures which he pioneered and that revolutionized the field of surgery. This study aims to analyze Europe’s efforts in utilizing al-Zahrawi’s landmark 30-volume encyclopedic work in developing the field of medicine. This research is qualitative with a historical approach. Data were collected using content analysis method, while data analysis was done descriptively. The results show that Europe used three methods to benefit from al-Zahrawi’s work in developing the field of medicine in European civilization. The first method was translation of al-Tasrif li man ‘Ajiza ‘an al-Ta’lif into various European languages. This initiative lasted almost 800 years. The second method was using al-Tasrif li man ‘Ajiza ‘an al-Ta’lif as reference material in medical schools in Europe. And the third method was to make al-Tasrif li man ‘Ajiza ‘an al-Ta’lif as reference material in writings of medical experts.